A dança e a promoção da saúde mental em um grupo de mulheres de uma academia na cidade de Novo Hamburgo-RS - Farias, Fernanda Elisa de (Universidade do Vale do Rio dos Sinos, 2022)
Through professional activity, Physical Education offers numerous possibilities of physical activities and increasingly deepens its commitiment to health. According to the World Health Organization (WHO) and the Brasilian Health Department (2020), physical activity is one of the main aspects to maintain the good health of individuals. These organizations draw attention to the importance of recently worsened mental health. Given this and among so may options, we chose the practice of dance as the focus of this research with the main objective of describing and analyzing the impact of dance on the mental health of women at the Centro de Artes Marciais e Treinamento Físico S.A.A.T.E. TEAM, in Novo Hamburgo/RS. This paper is characterized by a qualitative and descriptive research, making use of the following instruments: a semi-instructured interview and a script of observations. The interpretation of the data was done through a content analysis, pointing positive results to our problem, in which the interviwees reported significant changes in their mood, in the look to themselves, in the socializing with others, in the perception of their own bodies, among other transformations perceived as importante for the promotion of mental health.
Keywords: Dança; Atividade física; Saúde mental; Dance; Physical activity; Mental health